Existence criteria and classification schemes for positive solutions of second-order nonlinear difference systems. (28th September 2006) - Li, Wan-Tong; Huang, Can-Yun; Cheng, Sui Sun
Abstract : Classification schemes for positive solutions of a class of second-order nonlinear difference systems are given in terms of their asymptotic magnitudes; and necessary as well as sufficient conditions for the existence of these solutions are also provided. Finally, some examples are given to illustrate the main results.